Characterization of the Oxides Present in a Polydimethylsiloxane Layer Obtained by Polymerisation of Its Liquid Precursor in Corona Discharge. (23rd March 2015) - Groza, A.; Surmeian, A.
Abstract : By combining the reflection-absorption infrared spectral studies with the peak fitting analysis we determined the type of the silicon oxides present in polydimethylsiloxane layers obtained on germanium and aluminium substrates in corona discharges. We have also evidenced that the dependence of silicon oxides density on the corona discharge current intensity is related to the existence of a concurrent anodizing process occurring at the polymer/Al substrate interface. The morphology of the Al substrate surface investigated by scanning electron microscopy proved that the anodizing process occurs.